2023
DOI: 10.1002/1873-3468.14594
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin promotes vasculogenic mimicry by regulating the actin cytoskeleton in human breast cancer cells

Abstract: Vasculogenic mimicry (VM) is the formation of microvascular channels by cancer cells. VM requires cellular processes that are regulated by changes in cellular migration and morphology. Cofilin (CFL), a key regulator of actin depolymerization, has been reported to affect malignant phenotypes of cancer. We show that treatment with inhibitors of actin dynamics suppresses VM in MDA-MB-231 human breast cancer cells. We established CFL-knockout (KO) MDA-MB-231 cells and found that VM was attenuated in CFL-KO cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…To examine the function of DPY19L3 in VM genesis, we sought to establish HT1080 cell lines with deleted human DPY19L3 gene using CRISPR/Cas9 system, because we have reported that DPY19L3 is expressed in HT1080 cells [ 8 ] and HT1080 cells have enough VM formation capability [ 21 ]. Guide RNA sequences were designed at 2 close positions in exon 6 of DPY19L3 ( Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the function of DPY19L3 in VM genesis, we sought to establish HT1080 cell lines with deleted human DPY19L3 gene using CRISPR/Cas9 system, because we have reported that DPY19L3 is expressed in HT1080 cells [ 8 ] and HT1080 cells have enough VM formation capability [ 21 ]. Guide RNA sequences were designed at 2 close positions in exon 6 of DPY19L3 ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…VM-like network formation assay HT1080 and MDA-MB-231 cells, suspended in culture medium, were seeded at 3.2 × 10 3 and 2.0 × 10 4 cells/well, respectively, in a 96-well plate that was precoated with 40 µL/well Matrigel (Corning Inc., Somerville, MA, USA). The seeded cells were cultured at 37°C and photographed under a phase-contrast microscope (Leica DMi1; Leica Microsystems GmbH, Wetzlar, Germany) [21].…”
Section: Mtt Assaymentioning
confidence: 99%